Rick Steves' Europe [videorecording (DVD)] : a symphonic journey - Steves, Rick, 1955-; Miropolsky, Michael; Smith, John Stafford, 1750-1836; Damrosch, Walter, 1862-1950; Strauss, Johann, 1825-1899; Wagner, Richard, 1813-1883; Smetana, Bedřich, 1824-1884; Verdi, Giuseppe, 1813-1901; Elgar, Edward, 1857-1934; Grieg, Edvard, 1843-1907; Grieg, Edvard, 1843-1907; Berlioz, Hector, 1803-1869; et al. (Back Door Productions, 2013)
"Just as travel broadens one's perspective, so can music. People of every nation have music that sets their patriotic spirit soaring. In this hour-long concert special, Rick Steves teams up with the Cascade Symphony Orchestra on a musical tour that begins in the USA, then touches down in seven different European countries. For each stop, Rick paints the cultural context in words, and then the orchestra plays stirring anthems--from Strauss, Wagner, Smetana, Verdi, Elgar, Grieg, Berlioz--each accompanied by glorious video footage of the composer's homeland. The finale, Beethoven's Ode to joy, celebrates a continent whose motto is "united in diversity."